The Effect of Hypnoparenting To Toddler’s Malnutrition Status In Kebon Padangan Village, Pupuan Sub-District, Tabanan - Bali - Purnamayanthi, Pande Putu Indah; Ekajayanti, Pande Putu Novi; Adhiestiani, Ni Made Egar; Widiyanthi, Ni Made (STRADA : Jurnal Ilmiah Kesehatan, 2021)
There are a big numbers of problem related to malnutrition within these ages. Malnutrition as a health status is determined by weight for age index which ranged around -3 to -2 from standard deviation (SD). This study used pre-experiment one group pre-test – post-test design. Non-random purposive sampling was utilized to meet the sample criteria of mother who has children under 5 years with malnutrition status that did a health visit to Kebon Padangan Village Health Care Center. Data was collected with questionnaire and then analyzed by Wilcoxon Matched Pair test. After treated with hypnoparenting, the children were underwent anthropometric measurement every month in order to determine their nutritional status based by weight for age index. Average value before the treatment was -2.823 and then changed to average number of -2.403 after the intervention.